The Effect of Price Perception And Brand Image On Satisfaction For Customer Loyalty At Tempe Herber (HB) Factory - Fitria Riskiana Ritonga; Zulkifli Musannip Efendi Siregar; Mulya Rafika (PT Mattawang Mediatama Solution, 2022)
The purpose of this study was to determine the effect of price perception on loyalty, price perception on satisfaction, brand image on loyalty, brand image on satisfaction, satisfaction with loyalty, price perception on loyalty through satisfaction, brand image on loyalty through satisfaction at the tempe harber factory. The research that has been done is using quantitative research methods. In this study the population is unknown so I used Ruus Lemeshow so that the sample used was 100 people. While the data collection technique was by distributing questionnaires to consumers at the Tempe Harber factory, by measuring the coefficients using a Likert scale. The research also uses smartPLS3 software. PLS (partial least square) is a structural equation analysis (SEM) which can simultaneously test the measurement and structural measurement models. From the results of research that has been done, it can be seen that consumer satisfaction can mediate price perception on loyalty, and satisfaction can also mediate brand image on loyalty, price perception has no positive and significant effect on loyalty, price perception has a positive effect on satisfaction, while brand image has a positive effect. and significantly on loyalty and brand image a positive and significant effect on satisfaction.